SPREAD THE MALLOPHAGS OF CHICKENS IN FARMS OF POLTAVA REGION - Хижня, Л. Ю. (Scientific Progress & Innovations, 2013)
Research has found widespread Mallophags of chickens in farms in the Poltava region (Zenkov, Pyryatyn, Gadyach and Carlovka region). Extensity of infestation averaged 53,3 % to the intensity of infestation 3,8 ± 0,01 ekz./10х10 cm of the bird's body. On the territory of the Poltava region in chickens has found four types Mallophags: three kinds of family Menoponidae (Menopon gallinae, Menacanthus stramineus, Menacanthus cornutus) and one species of the family Goniodidae (Goniocotes hologaster).